Full scale rotor blade deformation measurements in comparison with aeroelastic simulations based on measured high-resolution wind fields. Issue 5 (September 2020) - Lehnhoff, S; Sekar, AP Kidambi; van Dooren, M F; Kühn, M; Seume, J R
Abstract: Aeroelasticity is one of the biggest challenges in wind turbine rotor design, as the length of rotor blades increases which comes along with a slenderer design. The knowledge of the aeroelastic turbine behavior is of great importance. A comparison to field measurements is of huge importance when validating aeroelastic tools. However, the measurement of deformation and torsion in the field is not trivial and the conduction of realistic post-test simulations is a challenge. One crucial factor for these simulations is the wind field, which needs to be captured in a high spatial and temporal resolution. In this paper, the results of deformation measurements conducted in the field with an optical measurement method called Digital Image Correlation (DIC) on one rotor blade will be shown and compared to aeroelastic post-test simulations using highly resolved wind fields measured with a SpinnerLidar.